Effect of antiepileptic drugs on bone metabolism in children using biochemical markers: a case control study - Rajan, Gopika V.; Sreenivasaiah, Bharathi; Lunavath, Narayana; Yerroju, Kodandapani (International Journal of Contemporary Pediatrics, 2023)
Background: Most epileptic patients are diagnosed and treated in childhood and adolescence and this period is crucial in attaining peak bone mass. Few studies are conducted on children showing long term effects of AEDs on bone metabolism. So, the present study was conducted to evaluate correlation of long-term uses of AEDs with changes in bone metabolism using biochemical marker. Methods: Total of 140 subjects divided into 70cases - Epileptic children aged 1 to 14 years who are on AEDs for at least 6months and 70 Controls- Children aged 1 to 14 years not on AEDs. Semi structured questionnaire was used to collect demographic data. Venous blood samples were collected and sent for laboratory investigations like Serum vitamin D, serum calcium, serum phosphorus, Parathyroid hormone and alkaline phosphatase levels. Results: Mean age of study population in cases was 7.74±4.43 years and in controls was7.65±3.72 years. Mean vitamin-D, calcium, phosphorus decreases while PTH and ALP increases with duration of treatment in epileptic children with a statistically significant difference between them (P<0.05). Mean serum vitamin D level in cases and in controls was with no statistical significant difference between two groups. Mean serum calcium, phosphorus, parathormone and alkaline phosphatase levels in cases and controls all had a statistically significant mean difference between two groups. Serum vitamin-D, serum calcium, serum phosphorus was low in patients treated with enzyme inducing when compared to non-enzyme inducing drugs in epileptic children with a statistically significant difference between them (P<0.05). Serum vitamin-D, serum calcium, serum phosphorus was high in patients on monotherapy when compared polytherapy in epileptic children with a statistically significant difference between them (P<0.05). Conclusions: Present study shows that children on AEDs for longer duration had low bone mineral parameters when compared to normal children. The study emphasizes that mineral levels need to be monitored in epileptic patients as they are at a higher risk of falling and bone fractures.